The mechanism and efficacy of GLP-1 receptor agonists in the treatment of Alzheimer’s disease - Du, Haiyang; Meng, Xiaoyu; Yao, Yu; Xu, Jun (Frontiers in Endocrinology, 2022)
Since type 2 diabetes mellitus (T2DM) is a risk factor for Alzheimer’s disease (AD) and both have the same pathogenesis (e.g., insulin resistance), drugs used to treat T2DM have been gradually found to reduce the progression of AD in AD models. In these drugs, Glucagon-like peptides 1 receptor (GLP-1R) agonists are more effective and have fewer side effects. GLP-1R agonists have reducing neuroinflammation and oxidative stress, neurotrophic effects, decreasing Aβ deposition and tau hyperphosphorylation in AD models, which may be a potential drug for the treatment of AD. However, this needs to be verified by further clinical trials. This study aims to summarize the current information on the mechanisms and effects of GLP-1R agonists in AD.